P-412 3D live-imaging reconstruction of the human embryo implantation ex vivo. (30th June 2022) - Ojosnegros, S; Godeau, A; Aroca, E; Solé, M; Parriego, M; Boada, M; Veiga, A; Lesman, A; Tchaicheeyan, O; Goren, S; Seriola, A
Abstract: Study question: How do human embryos implant in physiological conditions and develop beyond blastocyst stage? Summary answer: Human embryos apply forces during invasion of the matrix, the mural trophectoderm undergoes a quick compaction leading to a fast radial expansion of polar side What is known already: Human embryos can be cultured beyond blastocyst stage using supplements of animal origin, such as fetal bovine serum. However, two main issues limit our understanding of the implantation of the human embryo. First, human embryos do not express fluorescent proteins, severely limiting the access to advanced live-imaging tools. Second, the animal serums may not represent the physiological peri-implantation conditions of the human embryo, thus limiting the reproducibility of the in vitro experiments. Here we combine label-free multiphoton imaging with media formulations including clinical-grade protein supplements from human plasma unlocking the observation of the human embryo in 3D and physiological conditions Study design, size, duration: We have cultured 150 human embryos from D3 until blastocyst stage and also more than 600 mouse embryos from zygote until blastocyst stage and then transferred them into a 3D implantation platform. All embryos were supplemented with clinical-grade human-derived serum, which is rich in globulins and growth factors, and commercial basal media. The implantation was monitored for 3-to-5 days up until day 11. Traction-force microscopy and molecular imaging was employed to quantify implantation markers. Participants/materials, setting, methods: Implantation was measured using our novel version of traction-force microscopy, which reveals the force applied by entire embryos during live-imaging experiments. Multiphoton illumination of autofluorescent molecules allows to reconstruct images of live human embryos on 3D at unprecedented resolution. Key molecular markers for the formation of the epiblast rosette (OCT4), extra-embryonic visceral endoderm (GATA4), extra-embryonic ectoderm and trophoblast (CDX2) and primary yolk sac and pre-amniotic cavity were reconstructed in 3D using high resolution confocal imaging. Main results and the role of chance: The implantation of human embryos was visualized in 3D movies at high resolution, during time-resolved experiments and compared to implantation in mouse embryos. Human embryos undergo a remarkable compaction upon attachment of the polar trophectoderm and thereafter they implant by engaging the matrix through many different points (>8). The post-implantation compaction leads to a strong invasion of the polar trophectoderm, digging large holes in the matrix and expanding radially. Some trophoblast cells escape the embryo colonizing the matrix. Human embryos expressed the correct pattern of molecular markers by day 11 of culture. Actin staining and OCT4 expression revealed the formation of a central rosette defining the pre-amniotic cavity. GATA6 expression defined the visceral endoderm and the formation of a primordial yolk sac. Mouse embryos conversely, compact upon implantation of the mural trophectoderm and are less invasive, typically anchoring to the matrix through 2-to-3 points. Post-implantation culture of mouse embryos starting at zygote was possible until the formation and large expansion of the amniotic cavity, which constituted 2/3 of the whole embryo size, corresponding with the initial steps of gastrulation, longer than any previous protocol Transfer of mouse blastocysts back to receptive mothers resulted in birth of viable litter. Limitations, reasons for caution: This study has been performed with human embryos ex vivo using bioengineering technology to implant embryos outside the mother uterus. The bio-compatibility of our serum supplements was validated by live birth of transferred embryos in animal models, but would require further evaluation in clinical trials. Wider implications of the findings: Our work stresses the safety and efficiency of supplementing embryo culture and particularly embryo transfer, with human plasma-derived serums of clinical-grade. The correct expression of main molecular markers indicates that this type of supplementation promotes implantation physiologically, which opens the possibility to employ these serums in the IVF laboratory. Trial registration number: Not applicable